1994
DOI: 10.1159/000177807
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin C Intake Influence the Rate of Tyrosine Catabolism in Premature Babies?

Abstract: A study was conducted to investigate the relationship between vitamin C intake and the rate of tyrosine catabolism in premature babies. A 13C tyrosine breath test was developed for the measurement of tyrosine catabolism. Premature babies were randomly allocated to receive a daily intake of vitamin C which ranged from 8 to 100 mg/kg body weight, for 5 days. Tyrosine catabolism was measured at the beginning and the end of this period. Daily intakes of vitamin C of 20 mg/kg or more elicited a greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The Expert Panel recommended a higher level than the 6 mg/100 kcal recommended for term infants (Raiten et al, 1998a) because the needs of preterm infants for growth and development are higher than those of term infants, and to prevent or ameliorate oxygen toxicity of prematurity. Total daily intakes of 20 mg/kg, or up to 100 mg/(kg ⅐ d) for five days (ϳ17-83 mg/100 kcal) significantly increased the rate of tyrosine catabolism in preterm infants in a recent, although as yet not confirmed, study in which the in vivo 13 C-labeled tyrosine breath test was used (Powers et al, 1994). One current domestic formula contains 20 mg of vitamin C/100 kcal.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Expert Panel recommended a higher level than the 6 mg/100 kcal recommended for term infants (Raiten et al, 1998a) because the needs of preterm infants for growth and development are higher than those of term infants, and to prevent or ameliorate oxygen toxicity of prematurity. Total daily intakes of 20 mg/kg, or up to 100 mg/(kg ⅐ d) for five days (ϳ17-83 mg/100 kcal) significantly increased the rate of tyrosine catabolism in preterm infants in a recent, although as yet not confirmed, study in which the in vivo 13 C-labeled tyrosine breath test was used (Powers et al, 1994). One current domestic formula contains 20 mg of vitamin C/100 kcal.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Levine et al (1939) reported that high doses of parenteral vitamin C, up to 200 mg/single dose, in a total of 525 mg during a 4-day period, given to five premature infants fed dried cow milk without added vitamins C or B, resulted in a rapid decline in urinary tyrosine as measured by the Millon reaction. Powers et al (1994), using a 13 C-labeled tyrosine breath test, evaluated the metabolism of tyrosine in 25 preterm infants, whose GA was 25-35 weeks and BW was less than 1900 g, who received vitamin C supplements. Total daily intake of vitamin C was 8 -100 mg/kg for a 5-day period.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Copper in the form of copper sulfate may also inhibit tyrosinase activity. 78,79 It has also been suggested that the selective toxicity of ascorbate in malignant cells may be due to reduced levels of antioxidant enzymes, catalase, superoxide dismutase, and glutathione peroxidase 80 in these cells, leading to cellular damage through the accumulation of hydrogen peroxide. 44,74,[81][82][83][84][85] There is a 10-to 100-fold greater content of catalase in normal cells than in tumor cells.…”
Section: González Et Almentioning
confidence: 99%
“…The increased levels hydrogen peroxide, upon administration of Vitamin C, leads to accumulation of this ROS in cancer cells, which have amount of catalase of 10-to 100 times lower than the normal ones, and this explains the selective toxicity of high concentration of Vitamin C for cancer cells, as compared to the normal ones. [55][56][57][58][59][60] In addition to Vitamin C per se, some products of Vitamin C metabolism have shown anticancer properties; among others: dehydroascorbic acid, 2,3-diketogulonic acid, and 5-methyl 1-3,4-dehydroxytetrone. 27,28,[60][61][62][63] Secondary anticancer properties of Vitamin C include: I.…”
mentioning
confidence: 99%